Effective neutralization of chemical warfare agents (HD, VX) by Me-DABCOF: a small molecule with dual action. Issue 83 (30th September 2019) - Karton-Lifshin, Naama; Katalan, Shahaf; Columbus, Ishay; Chen, Ravit; Yehezkel, Lea; Madmon, Moran; Dagan, Shai; Elias, Shlomi; Fridkin, Gil; Zafrani, Yossi
Abstract : Me-DABCOF, a mild universal, non-corrosive, water-soluble decontamination agent that effectively neutralizes chemical warfare agents (HD, VX). Abstract : The ability of mono N -methyl-1, 4-diazabicyclo[2.2.2]octane fluoride (Me-DABCOF, 1 ) to act as a bifunctional reagent that effectively and universally neutralizes both the persistent and extremely toxic blister agent HD and the nerve agent VX in nearly neutral aqueous solution, alumina powder or a hydrogel formulation, is described.